ATTRACTION OF TEPIAN BANDAR SUNGAI JANTAN SIAK DISTRICT - Ahmad, Rummana Zahara; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Tepian Bandar Sungai Jantan Area in Siak District is one of the new tourist attractions in Siak District. As one of the new tourist attractions in Siak District, it is necessary to do an assessment of the attraction of existing attractions to be able to attract visitors. The response in the world of tourism is the opinion or perspective of visitors in understanding a tourist destination. This study aims to find out how tourists respond about the new attraction of Tepian Bandar Sungai Jantan Siak District. This research is using descriptive quantitative methods to examine the issues raised. The sample used was 100 people taken using accidental sampling. While the data collection techniques in this research used observation, interviews, and questionnaires using a Likert scale as a measurement tool. Based on the results of the research, Tourist Attraction of Tepian Bandar Sungai Jantan Siak District with the conclusion of the research in the good category.Â Keywords : Tourism, Attraction, Area, Visitors.